Growth and Yield of Different Varieties of Chickpea (Cicer arietinum L.) as Influenced by the Phosphorus Nutrition under Rainfed Conditions on Vertisols - Neenu, S.; Ramesh, K.; Ramana, S.; Biswas, A. K.; Rao, A. Subba (International Journal of Bio-resource and Stress Management, 2014)
A field experiment was carried out in Indian Institute of Soil Science, Bhopal during the rabi season 2011-12 to study the effect of different doses of phosphorus on the growth and yield of different varieties of chickpea (Cicer arietinum L.) under rainfed conditions in vertisols. The experiment was laid out in a Split plot design with three replications. There were four phosphorus levels viz., 0, 30, 60 and 90 kg P2O5 ha-1 and four varieties of chickpea viz., JG 16, JG 11, JG 315 and JG 218. Barring JG 11, application of phosphorus from 0 to 60 kg ha-1 resulted in a linear increase in yield and yield attributing characters in rest of the varieties. Although there was no significant difference in seed yield among the varieties, application of either 60 or 90 kg P2O5 ha-1 produced significantly higher seed yield over other doses of P. The application of phosphorus above 60 kg ha-1 has significantly increased the grain phosphorus content in all the four varieties but the interaction effect was not significant. A significant increase of grain phosphorus uptake with phosphorus nutrition was also observed in all the varieties.